2022
DOI: 10.3390/jcm11092365
|View full text |Cite
|
Sign up to set email alerts
|

There Is a Differential Pattern in the Fatty Acid Profile in Children with CD Compared to Children with UC

Abstract: Background: Crohn’s disease (CD) and Ulcerative Colitis (UC) are classified as inflammatory bowel diseases (IBD). Currently, an increasing number of studies indicate that the metabolic consequences of IBD may include abnormalities in the fatty acid profile. The aim of this study was to compare fatty acid concentrations in IBD in order to identify differences between CD and UC and differences between the phases of both diseases. Methods: Sixty-three adolescent patients with CD (n = 33) and UC (n = 30) aged 13.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
1
1
0
3
Order By: Relevance
“…Studies have also shown a higher activity of 5-LOX in patients compared to the healthy control group. 5-HETE is a strong activator of neutrophilia [8,38]. These results are consistent with a study conducted by Masoodi and others.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have also shown a higher activity of 5-LOX in patients compared to the healthy control group. 5-HETE is a strong activator of neutrophilia [8,38]. These results are consistent with a study conducted by Masoodi and others.…”
Section: Discussionsupporting
confidence: 92%
“…Kikut та співавт. також показали, що пальмітинова кислота, визначена в плазмі крові підлітків, пов'язана зі стадією ремісії при ХК, тоді як лінолева кислота -з активною фазою цього захворювання [21]. Barnes Патологія кишечника / Bowel Pathology високе споживання з їжею жирних кислот, включно з міристиновою кислотою, з підвищеним ризиком розвитку НВК [22].…”
Section: вступunclassified
“…Патологія кишечника / Bowel Pathology вати активацію нуклеарного фактора транскрипції κB (НФ-κB) та ІЛ-8. Ще лауринова кислота може бути антагоністом імунної системи, стимулюючи білок толподібного рецептора 4 (ТПР-4) та утворюючи монолаурин у кишечнику, який, у свою чергу, має антимікробну дію [21].…”
Section: примітки: вірогідна різниця порівняно з контролем: *** -P < ...unclassified
See 1 more Smart Citation
“…MCFAs such as heptanoate, octanoate and nonanoate, exhibit markedly decreased levels in IBD patients ( 134 ). In pediatric patients, there were variations of lauric acid between CD and UC, and higher levels of lauric acid were observed during UC active phases compared to remission ( 135 ). In summary, reduced levels of MCFAs are common among IBD patients, and proportions of MCFAs differ between CD and UC.…”
Section: Medium-chain Fatty Acidsmentioning
confidence: 99%